THE IMPLEMENTATION OF COOPERATIVE LEARNING APPROACH PAIR CHECKS TO IMPROVE MATH LEARNING OUTCOMES STUDENTS CLASS VIII3 SMP N 25 PEKANBARU - Addini Maulida Istia Maulida Istia; Zulkarnain '; Putri Yuanita Putri Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study is a class act. The study is based on classroom learning conditions of class VIII3 SMP 25 Pekanbaru are still problematic, where the value of learners is below the KKM and learning are still centered on the teacher. Therefore, this study aims to improve learning process and improve mathematics learning outcomes. The subject of this research is VIII3 grade students of SMP 25 Pekanbaru on odd semester 2014/2015 in academic year, which amounts to 40 people consisting of 13 men and 27 women with heterogeneous levels of ability. This study consisted of two cycles, each cycle consisting of four phases, namely planning, action, observation and reflection. Each end of the cycle performed quiz. Data collected through observation and tests in the form of a quiz. Data analysis technique in this research is the analysis of qualitative data and quantitative data analysis. The results of research on the observation sheet showed the activity of teachers and learners increasingly performing well after doing the action. Based on the observations of researchers during the learning process in the classroom VIII3 SMP 25 Pekanbaru, most of the students were active in the learning process are implemented. Achievement attitude in its development more visible in working LKPD, as evidenced by an increase in the number of learners who achieve good and very good category. Same with the attainment of skills of students, number of learners who are skilled and skilled enough to rise. The percentage of students who achieve the KKM knowledge base score, quiz I (first cycle), replicates quiz II (second cycle) respectively is 42.5%, 65%, and 67.5%. Action is successful if the state after the action better. The results showed that the application of the approach to the pair checked into cooperative learning can improve the learning process and improve learning outcomes VIII3 grade math students SMP 25 Pekanbaru.Keywords: Results of mathematics learning, cooperative learning, Pair check, action research.